STANDARDIZATION OF THE POSSIBILITY OF SPECIALISED NURSING CARE AFTER CARDIAC CATETRIZATION - Klemsová, Ludmila; Žiaková, Katarína (Profese Online, 2014)
Aim: Main aim of this report was to determine the possibilities of standardisation specialized nursing care for decannulation of the sheath from arteria radialis, femoralis by using analysis of literary sources.Introduction: Processual standards nursing procedures at operation and their importance for quality evaluation are significantly enforced by nurse. The procedure of the decannulation of sheath from arterial basin can influence the final effect of catheterization. The sheath standardisation is an important phenomenon contributing to reduction of complications and the quality of the operation as well.Methods: The methodology is based on research of professional articles from PubMed, Medline, Cochrane, MedscapeNurses databases for a period 1998-2010. It was used a Boolean operator (or/and), with entering the key words. It was found 59 references by using key words,then we worked with 16 references, which were relevant for the purpose of our report.Results: The references point to the fact that nursing standards for decannulation of the sheath are often based on conlusions of the nursing research (EBP). They focus on a reduction of bleeding at the injection site from the beginning of the heart catheterization. The standards are focusing on manners and the the length of the compression on arteria femoralis, arteria radialis. According to the references the importance is based on elimination of complications (hematoma, hemorrhage) by introducing the mechanical compression devices, but mainly by high-skilled nursing staff trained in manners of compression and accuracy of application compression devices. In references is emphasized an early patient's mobilization after catheterization. This is possible in compliance with the conditions set out by nursing standard for decannulation of the sheath.Conclusion: The nursing standard is an important part contributing to the reduction of complications and improving patient's comfort. It is particularly important platform abroad.
Keywords: nursing; femoral; radial; standard; catetrization